2019
DOI: 10.21271/zjpas.31.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Detection of Metallo-β –Lactamase Producing Pseudomonas aeruginosa Isolates From Different Clinical Infections in Erbil

Abstract: Metallo-β-lactamase (MBL) producing Pseudomonas aeruginosa has been documented to be a critical nosocomial infection. Itwas continuous intrinsic and acquired resistance to a various group of antimicrobial agents and its resistance ability to develop multidrug resistance lead to a severe therapeutic problem. The study aimed to identify the molecular characterisation of clinical isolates of Metallo-β-lactamase P. aeruginosain Erbil hospitals. This study was carried out during the period from October 2017 to Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…P. aeruginosa isolates were highly susceptible (low resistance) to meropenem 13/30 (43.3%) and imipenem 9/30 (30%) (see Table 3). The findings of this study demonstrated that all P. aeruginosa isolates were completely resistant 100% to piperacillin and it was consistent with the findings from a previous investigation in Irbil, Iraq, found that all isolates of P. aeruginosa were piperacillin-resistant 100% [32]. According to the data from earlier studies found different results from ours, which were (32% and 37%), respectively [33,34].…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 91%
“…P. aeruginosa isolates were highly susceptible (low resistance) to meropenem 13/30 (43.3%) and imipenem 9/30 (30%) (see Table 3). The findings of this study demonstrated that all P. aeruginosa isolates were completely resistant 100% to piperacillin and it was consistent with the findings from a previous investigation in Irbil, Iraq, found that all isolates of P. aeruginosa were piperacillin-resistant 100% [32]. According to the data from earlier studies found different results from ours, which were (32% and 37%), respectively [33,34].…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 91%